Determination of the Critical Success Criteria for Public-Private Partnership (PPP) Projects in Turkey - Okudan, Ozan; Budayan, Cenk (GAZI UNIV, 2021)
Although the PPP concept is preferred for delivering mega-infrastructure projects in developed and developing countries in recent years, the success of these projects has been criticized. Especially, in Turkey, there are intensive criticisms about these project's success concerning economic and environmental aspects. Determining the success criteria and their importance levels are key to remedy these issues since project teams can identify the clear set of the objectives of these projects, and all processes in PPP projects can be performed for achieving these objectives. There are studies about the success criteria of PPP projects in the literature. However, none of these studies focuses on Turkey. Given the fact that success criteria vary concerning the country's cultural, economic, and traditional background, success criteria specific to Turkish PPP projects must be determined. Additionally, success criteria also vary among the different stakeholders, and unawareness of these differences puts the project success at risk. Thus, differences in perspectives of the public and private sectors were also investigated in this study. Firstly, 15 success criteria were extracted from the literature. Then, a questionnaire survey was organized to collect expert's opinion about the importance of these criteria. 33 experts participated in this questionnaire survey. The data collected through the questionnaire survey was analyzed by using factor analysis and 4 factors were determined at the end of this analysis. Finally, the Mann-Whitney U test was performed to investigate the differences in perspectives of the public and private sectors. The factor analysis shows that the most important factors are project delivery and the project's contribution to the public's prosperity. Besides, the findings indicated that stakeholders have considerable disagreements on three criteria, namely quality of the project with meeting output specifications, reliable and quality public service, and reduced public sector administrative costs.
Keywords: PPP; factor analysis; Turkish construction industry; success criteria; Turkish ppp market; project success; KEY PERFORMANCE INDICATORS; EXPLORATORY FACTOR-ANALYSIS; SAMPLE-SIZE; ROAD PROJECTS; PERSPECTIVES; PERCEPTION; Engineering